2006
DOI: 10.1093/jac/dkl391
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of ciprofloxacin-resistant Salmonella enterica serovar Typhi and Paratyphi A causing enteric fever in India

Abstract: To our knowledge this is the first report of molecular characterization of S. Typhi with full resistance to ciprofloxacin. Notably, the presence of a plasmid-borne integron in ciprofloxacin-resistant S. Typhi may lead to a situation of untreatable enteric fever.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
98
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 29 publications
5
98
1
Order By: Relevance
“…This highly resistant ciprofloxacin S. Typhi strain is still susceptible to most of the first-line antibiotics, and this is different from the other cases reported in India where S. Typhi strains are resistant to first-line antibiotics as well as fluoroquinolones [28,29,30,31].…”
Section: Discussioncontrasting
confidence: 69%
“…This highly resistant ciprofloxacin S. Typhi strain is still susceptible to most of the first-line antibiotics, and this is different from the other cases reported in India where S. Typhi strains are resistant to first-line antibiotics as well as fluoroquinolones [28,29,30,31].…”
Section: Discussioncontrasting
confidence: 69%
“…A single mutation in quinolone-resistance-determining region of gyr A gene is sufficient to confer resistance to NA and reduced susceptibility to fluoroquinolones. The continued use of ciprofloxacin against NA R strains has led to a steady creep in ciprofloxacin MICs [7,16,19] along with further mutations at the same locus, resulting in recent emergence of fully resistant strains [7,8,[20][21][22]. Saha et al, in 2006, reported a highly ciprofloxacin-resistant S. Typhi strain with the MIC as high as 512 μg/mL from Bangladesh [23].…”
Section: Discussionmentioning
confidence: 99%
“…This result may be due to the presence of a tetracycline resistance marker on a large-sized or defective plasmid [30,31]. Moreover, ciprofloxacin and nalidixic acid resistance were not transferred through conjugation and transformation, and this may be due to the chromosomal origin of nalidixic acid and ciprofloxacin resistance [32]. Tetracycline, norfloxacin, amoxycillin/clavulanic acid, trimethoprim/sulfamethoxazole, and ciprofloxacin thus have a greater advantage against resistance, as resistance to these are not transferrable by horizontal gene transfer thereby restricting the spread of drug resistance.…”
Section: Discussionmentioning
confidence: 99%